Career Entry Skills — Gap in the Guidance Chain - Clark, Andrew K. (Canadian Journal of Counselling and Psychotherapy, 2012)
Strengthening of career entry skills is advocated as a bridgeto enable job-seekers of high-school age to successfully enter the world ofwork. Research is reported which indicates that the career entry skills possessed by job applicants in this age group are not rated highly by personnel officers, nor do they figure largely in extent or importance invocational guidance programs. A proposed guidance curriculum unit on career entry skills is outlined and discussed.